KEMBANG LAN WIT-WITAN SEBAGAI NAMANAMA DESA DI KECAMATAN KABUH JOMBANG: PERSPEKTIF WHORF - Efendi, Agik Nur (Pusat Pengembangan Bahasa IAIN Tulungagung, 2017)
This article discusses the language used to name the village in Jombang, East Java from the perspective of Whorfâs hypothesis stating that individualâs frst language inï¬uence his idea and thought on the reality. In addition, there is also correlation between language and culture both subordinatively and coordinatively. This article aims at describing Whorfâs hypothesis on how language, culture, and though give inï¬uence on the naming of villages in Kabuh, Jombang, East Java. The fnding shows that the villages are named after the local name of plants and ï¬owers such as Drenges, Tales, Jati Raja, Kedung Jati, Randu Alas, Kedung Pandan. This fnding affrms that the way they name their villages is inï¬uenced by they perceive their surrounding environment.